Adaptation to chronic continuous hypoxia potentiates Akt/HK2 anti-apoptotic pathway during brief myocardial ischemia/reperfusion insult - Kolar, David; Gresikova, Milada; Waskova-Arnostova, Petra; Elsnicova, Barbara; Kohutova, Jana; Hornikova, Daniela; Vebr, Pavel; Neckar, Jan; Blahova, Tereza; Kasparova, Dita; Novotny, Jiri; Kolar, Frantisek; et al. (Molecular and cellular biochemistry, 2017)
Adaptation to chronic hypoxia represents a potential cardioprotective intervention reducing the extent of acute ischemia/reperfusion (I/R) injury, which is a major cause of death worldwide. The main objective of this study was to investigate the anti-apoptotic Akt/hexokinase 2 (HK2) pathway in hypoxic hearts subjected to I/R insult. Hearts isolated from male Wistar rats exposed either to continuous normobaric hypoxia (CNH; 10% O2) or to room air for 3 weeks were perfused according to Langendorff and subjected to 10 min of no-flow ischemia and 10 min of reperfusion. The hearts were collected either after ischemia or after reperfusion and used for protein analyses and quantitative fluorescence microscopy. The CNH resulted in increased levels of HK1 and HK2 proteins and the total HK activity after ischemia compared to corresponding normoxic group. Similarly, CNH hearts exhibited increased ischemic level of Akt protein phosphorylated on Ser473. The CNH also strengthened the interaction of HK2 with mitochondria and prevented downregulation of mitochondrial creatine kinase after reperfusion. The Bax/Bcl-2 ratio was significantly lower after I/R in CNH hearts than in normoxic ones, suggesting a lower probability of apoptosis. In conclusion, the Akt/HK2 pathway is likely to play a role in the development of a cardioprotective phenotype of CNH by preventing the detachment of HK2 from mitochondria at reperfusion period and decreases the Bax/Bcl-2 ratio during I/R insult, thereby lowering the probability of apoptosis activation in the mitochondrial compartment.
Keywords: Mitochondria; reperfuzní poškození myokardu; Male; Rats, Wistar; srdeční mitochondrie; Myocardial Reperfusion Injury; Myocardium; Hypoxia; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; mužské pohlaví; potkani Wistar; Mitochondria, Heart; krysa rodu Rattus; Animals; zvířata; Protein kinase B/Akt; Rats; hexokinasa; Ischemia/reperfusion; Heart; myokard; Hexokinase